TELAAH KESIAPSIAGAAN MANAJEMEN TERHADAP KONDISI DARURAT KEBAKARAN DI PT. X (PULP & PAPER) TAHUN 2017 - Bagas Satrio Priambudi; Bina Kurniawan; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Fire is one of the disasters that can cause loss of life, material, decreased productivity, business interruption, and social losses. Fire prevention can be created by the policy of management to overcome fire, the organization of fire prevention, the existence of fire prevention procedures and fire training. The purpose of this study is to analyze the preparedness of management in the face of fire emergency at PT. X. This research is descriptive research. Subjects in this study were OHS managers, Fire Supervisors, Head of Security and Role of Fire. Data obtained through in-depth interviews and observation methods. The results of this study indicate that there is fire management covering procedures, risk assessment, human resources provision, emergency relief team, and fire prevention facilities and infrastructure running in accordance with its function, the fire management was established by the manager although not yet wearing the mark A special identifier, all fire fighters teams have been trained, already have coordinated emergency response procedures with local firefighters, have posts to anticipate emergencies, periodic training programs, have not held meetings every three months, have not held any training every six months Once, there is a procedure about the training procedures. The advice of this study for management is to provide a special identification to the fire management team to identify the identity and authority of the fire prevention team, conduct fire-fighting team meetings, at least every three months to discuss issues related to preparedness and fire prevention tips and to include All residents of the building, at least every six months to carry out fire rescue exercises to improve preparedness to cope with fires.